Coming to Grips with a Critical Methodology - Chew, Phyllis G. L. (Journal of Modern Languages, 2017)
This study considers the issues related to the critical methodology. The paper states that in such a methodology, different interdisciplinary perspectives become available since it is a methodology which acknowledges that social processes are dynamic and not static and that social phenomena are too complex to be dealt with adequately in only one field. It also mentions that a critical methodology offers the widest scope for a more significant and socially relevant discourse analysis which does not rum to separate theory from application.